Household transmission of SARS-CoV-2 in five US jurisdictions: Comparison of Delta and Omicron variants - Julia M. Baker; Jasmine Y. Nakayama; Michelle O’Hegarty; Andrea McGowan; Richard A. Teran; Stephen M. Bart; Lynn E. Sosa; Jessica Brockmeyer; Kayla English; Katie Mosack; Sanjib Bhattacharyya; Manjeet Khubbar; et al. (PLoS ONE, 2025)
Households are a significant source of SARS-CoV-2 transmission, even during periods of low community-level spread. Comparing household transmission rates by SARS-CoV-2 variant may provide relevant information about current risks and prevention strategies. This investigation aimed to estimate differences in household transmission risk comparing the SARS-CoV-2 Delta and Omicron variants using data from contact tracing and interviews conducted from November 2021 through February 2022 in five U.S. public health jurisdictions (City of Chicago, Illinois; State of Connecticut; City of Milwaukee, Wisconsin; State of Maryland; and State of Utah). Generalized estimating equations were used to estimate attack rates and relative risks for index case and household contact characteristics. Data from 848 households, including 2,622 individuals (median household size = 3), were analyzed. Overall transmission risk was similar in households with Omicron (attack rate = 47.0%) compared to Delta variant (attack rate = 48.0%) circulation. In the multivariable model, a pattern of increased transmission risk was observed with increased time since a household contact’s last COVID-19 vaccine dose in Delta households, although confidence intervals overlapped (0–3 months relative risk = 0.8, confidence interval: 0.5–1.2; 4–7 months relative risk = 1.3, 0.9–1.8; ≥8 months relative risk = 1.2, 0.7–1.8); no pattern was observed in Omicron households. Risk for household contacts of symptomatic index cases was twice that of household contacts of asymptomatic index cases (relative risk = 2.0, 95% confidence interval: 1.4–2.9), emphasizing the importance of symptom status, regardless of variant. Uniquely, this study adjusted risk estimates for several index case and household contact characteristics and demonstrates that few characteristics strongly dictate risk, likely reflecting the complexity of the biological and social factors which combine to impact SARS-CoV-2 transmission.